2021
DOI: 10.1073/pnas.2101485118
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype divergence supports long-term asexuality in the oribatid miteOppiella nova

Abstract: Sex strongly impacts genome evolution via recombination and segregation. In the absence of these processes, haplotypes within lineages of diploid organisms are predicted to accumulate mutations independently of each other and diverge over time. This so-called “Meselson effect” is regarded as a strong indicator of the long-term evolution under obligate asexuality. Here, we present genomic and transcriptomic data of three populations of the asexual oribatid mite species Oppiella nova and its sexual relative Oppi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 89 publications
4
39
0
Order By: Relevance
“…nova are cosmopolitan. Only females of the latter species were collected, in agreement with its reported asexual reproduction (Brandt et al 2021). Belbodamaeus (Lanibelba) palaciosi and S. (S.) elegans have been collected in cave soils, agricultural and natural areas, showing great capacity for adaptation to adverse conditions.…”
Section: Scheloribatidae: Oripodoideasupporting
confidence: 61%
“…nova are cosmopolitan. Only females of the latter species were collected, in agreement with its reported asexual reproduction (Brandt et al 2021). Belbodamaeus (Lanibelba) palaciosi and S. (S.) elegans have been collected in cave soils, agricultural and natural areas, showing great capacity for adaptation to adverse conditions.…”
Section: Scheloribatidae: Oripodoideasupporting
confidence: 61%
“…First, in the absence of recombination, haplotypes can diverge in what is known as the Meselson effect in ancient asexuals (Birky 1996;Welch et al 2000). Recent genomic data have demonstrated the Meselson effect and the long-term evolution in oribatid mites (Brandt et al 2021). Second, hybridization between divergent sexual progenitors instantaneously produces asexual lineages with high heterozygosity; this is the mechanism seen in nearly all parthenogenetic lizards (Fujita et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies using whole genomic-and transcriptomic-wide data have found evidence that is contrary to the expectation of mutation accumulation in asexual populations. Transcriptome-wide data from orib-atid mites revealed that purifying selection was more effective in the extremely old asexual lineages (∼10 million years old) than in sexual lineages (Brandt et al 2017(Brandt et al , 2021. Nonrecombining portions of the genome are expected to accumulate transposable elements (TE) and other repetitive content that leads to genomic degradation such as in the Y-chromosomes (Junakovic et al 1998;Bachtrog 2013).…”
mentioning
confidence: 99%
“…In addition, apomictic genomes exhibit significant levels of hemizygosity [ sensu Meselson effect; refer to (Brandt et al, 2021 ), also reviewed in (Hand and Koltunow, 2014 )], and repetitive element accumulation (Calderini et al, 2006 ). Whether these structural genomic features are the cause or a consequence of apomixis is still a subject of debate (Hand and Koltunow, 2014 ).…”
Section: Introductionmentioning
confidence: 99%